Survival : global politics and strategy. April-May 2025, (the International Institute for Strategic Studies, 2025)
Survival, the IISS's bimonthly journal, challenges conventional wisdom and brings fresh, often controversial, perspectives on strategic issues of the moment.In this issue: Sophia Besch and Tara Varma analyse the influence of the 'Make America Great Again' movement on the revisionist agenda in Europe Shashank Joshi evaluates the challenge of maintaining meaningful human control in decision-making as the role of artificial intelligence on the battlefield advances Matthew F. Cancian explores how the principle of 'denial over weeks' could save the United States from a prolonged and unwinnable war over Taiwan Dana H. Allin and Christopher S. Chivvis assess the impact of the early moves of Donald Trump's second administration on the relationship between Europe and the United States And nine other thought-provoking pieces, as well as our regular Book Reviews and Noteworthy column To read free articles from the journal, please visit its homepage at https://www.tandfonline.com/journals/tsur20.Editor: Dr Dana AllinManaging Editor: Jonathan StevensonAssociate Editor: Carolyn WestEditorial Assistant: Anna Gallagher
Keywords: Strategy.; Military policy.; Disarmament.; elektronické knihy; electronic books